Green synthesis of magnetic Fe3O4 nanoparticles using Couroupita guianensis Aubl. fruit extract for their antibacterial and cytotoxicity activities. (3rd April 2018) - Sathishkumar, G.; Logeshwaran, V.; Sarathbabu, S.; Jha, Pradeep K.; Jeyaraj, M.; Rajkuberan, C.; Senthilkumar, N.; Sivaramakrishnan, S.
Abstract: In the present study, a sustainable green chemistry approach was established to fabricate magnetic Fe3 O4 nanoparticles (Fe3 O4 NPs) using the aqueous fruit extract of edible C. guianensis (CGFE). Synthesized NPs were further confirmed with different high-throughput characterization techniques such as UV–visible spectroscopy, FT-IR, XPS, DLS and zeta potential analysis. Additionally, XRD, AFM, HRTEM and SQUID VSM demonstrate the generation of crystalline CGFe3 O4 NPs with mean diameter of 17 ± 10 nm. Interestingly, CGFe3 O4 NPs exhibit a stupendous bactericidal action against different human pathogens which depicts its antimicrobial value. A significant dose-dependent cytotoxic effect of CGFe3 O4 NPs was noticed against treated human hepatocellular carcinoma cells (HepG2).